Optimalisasi MGMP: Pengaruh Motivasi dan Keaktifan Guru Terhadap Profesionalisme Guru - Fitrianisa, Pipih; Paroli, Paroli; Apiatno, Apiatno (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of motivation (both intrinsic and extrinsic) and teachers’ level of participation in the Subject Teacher Forum (MGMP), as well as its impact on teacher professionalism in Sumedang Regency. This research employs a quantitative survey-based method involving 125 respondents. The survey instrument consists of a questionnaire covering variables of motivation (23 items), teacher participation (6 items), and teacher competence (12 items). The collected data were analyzed using inferential and differential statistical techniques, including descriptive analysis, prerequisite testing, and multiple linear regression with the assistance of SPSS software. The findings indicate that teacher motivation has a positive and significant effect on teacher professionalism. Furthermore, teachers’ active participation in MGMP activities also demonstrates a positive and significant influence on professionalism. Simultaneously, both motivation and participation exert a positive and significant combined effect on teacher professionalism in Sumedang Regency. Therefore, this study contributes an empirical model of the factors influencing teacher professionalism, particularly within the context of participation in MGMP activities. The results are expected to serve as a reference for stakeholders in designing and developing more effective MGMP programs to enhance teacher professionalism in the future.